2022
DOI: 10.1038/s41388-021-02148-y
|View full text |Cite
|
Sign up to set email alerts
|

The POU2F1-ALDOA axis promotes the proliferation and chemoresistance of colon cancer cells by enhancing glycolysis and the pentose phosphate pathway activity

Abstract: Cancer metabolic reprogramming enhances its malignant behaviors and drug resistance, which is regulated by POU domain transcription factors. This study explored the effect of POU domain class 2 transcription factor 1 (POU2F1) on metabolic reprogramming in colon cancer. The POU2F1 expression was analyzed in GEO dataset, TCGA cohorts and human colon cancer tissues by bioinformatics and immunohistochemistry. The effects of altered POU2F1 expression on proliferation, glucose metabolism and oxaliplatin sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…It can be seen by combining the specific position of five clusters from Figure 5 that early research around the year 2011, “study of tumor oxidative stress and inflammation signaling pathways and resistance mechanisms of different cancer types (cluster 4 and cluster 2)” had attracted a lot of attention in academia of this field. Afterward, “Study of cancer cell apoptosis pathway (cluster 1)” progressively gained importance around 2014, and some areas remain the hotpots until today, for example, “androgen receptor” (APY = 2018.82) ( 103 ), “glioblastoma” (APY= 2018.54) ( 79 ), and “transcription” (APY= 2018.15) ( 104 ). Notably, cluster 3 and cluster 5 (“study of cancer stem cells and autophagy”) are the two clusters that had the smallest APY compared with other clusters, and “metabolic reprogramming” (APY= 2019.39) ( 105 ), “microRNAs” (APY= 2019.05) ( 106 ) were mainly found lately.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen by combining the specific position of five clusters from Figure 5 that early research around the year 2011, “study of tumor oxidative stress and inflammation signaling pathways and resistance mechanisms of different cancer types (cluster 4 and cluster 2)” had attracted a lot of attention in academia of this field. Afterward, “Study of cancer cell apoptosis pathway (cluster 1)” progressively gained importance around 2014, and some areas remain the hotpots until today, for example, “androgen receptor” (APY = 2018.82) ( 103 ), “glioblastoma” (APY= 2018.54) ( 79 ), and “transcription” (APY= 2018.15) ( 104 ). Notably, cluster 3 and cluster 5 (“study of cancer stem cells and autophagy”) are the two clusters that had the smallest APY compared with other clusters, and “metabolic reprogramming” (APY= 2019.39) ( 105 ), “microRNAs” (APY= 2019.05) ( 106 ) were mainly found lately.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the PPP allows tumor cells to defend themselves against increased ROS levels caused by a rapid metabolism, as well as meet the elevated demand for nucleic acid and fatty acid biosynthesis [ 6 , 7 , 27 ]. Furthermore, the PPP has attracted attention as a potential target for antitumor therapy [ 28 ]. Our study indicates that G6PD, the first rate-limiting enzyme of the PPP, is a target of p52-ZER6, which binds to the G6PD promoter and enhances its transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“… 29 And the study of Lin et al found that POU2F1 directly bound to the ALDOA promoter and then decreased the sensitivity to oxaliplatin in colon cancer cells by enhancing glycolysis. 30 Furthermore, targeting metabolism reprogramming was an efficient method to overcome the chemoresistance of pancreatic ductal adenocarcinoma. 31 Consequently, targeting glycolysis has been indicated to be an effective means for overcoming chemoresistance, thereby improving cancer therapy.…”
Section: Discussionmentioning
confidence: 99%